2010
DOI: 10.3382/ps.2009-00232
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of algal and fish sources on the oxidative stability of poultry meat and its enrichment with omega-3 polyunsaturated fatty acids

Abstract: Human consumption of long-chain n-3 polyunsaturated fatty acids (LC n-3 PUFA) is below recommendations, and enriching chicken meat (by incorporating LC n-3 PUFA into broiler diets) is a viable means of increasing consumption. Fish oil is the most common LC n-3 PUFA supplement used but is unsustainable and reduces the oxidative stability of the mat. The objective of this experiment was to compare fresh fish oil (FFO) with fish oil encapsulated (EFO) in a gelatin matrix (to maintain its oxidative stability) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 26 publications
4
53
0
2
Order By: Relevance
“…Meat samples from broilers fed with BP were more susceptible to oxidation compared to control. The higher lipid content of thigh meat compared with breast meat is reflected in its lower oxidative stability because MDA content was more concentrated in the thigh meat (Rymer et al 2010). Significantly higher increase of MDA concentration was observed in muscles of experimental group, which is caused by higher amount of PUFA in these muscles.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Meat samples from broilers fed with BP were more susceptible to oxidation compared to control. The higher lipid content of thigh meat compared with breast meat is reflected in its lower oxidative stability because MDA content was more concentrated in the thigh meat (Rymer et al 2010). Significantly higher increase of MDA concentration was observed in muscles of experimental group, which is caused by higher amount of PUFA in these muscles.…”
Section: Resultsmentioning
confidence: 89%
“…The most strategies used to influence the fatty acid profile of broiler meat also require the addition of antioxidants to reduce the process of oxidation of lipids and thus to preserve the quality and shelf life of meat (Rymer et al 2010;Jaskiewicz et al 2014). Tres et al (2014) concluded that the tissue susceptibility to oxidation is dependent on their PUFA/a-tocopherol ratios.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study was concerned about a kind of n-3-fatty-acid-enriched marine microalgae (Schizochytrium type), which was reported as a cheaper and interesting source n-3 fatty acid than the other sources such as fish oil and plant oils (Rymer et al 2010). To the best of our knowledge, the utilisation of this n-3 fatty acid source is not well investigated in the poultry industry.…”
Section: Introductionmentioning
confidence: 99%
“…Pese que el rol de los triglicéridos en la oxidación de la carne es menor que el atribuido a los fosfolipídos algunos autores han demostrado que la composición de los primeros es importante para determinar el desarrollo de la oxidación y utilizan una ifórmula para calcular el índice de oxidación de esos lípidos (Rymer & Givens, 2010b) La oxidación lipídica ha sido correlacionada, además, con el contenido en hierro, humedad y proteína de la carne (Ang, 1988;Hidalgo, et al, 1992). El agua únicamente actúa como solvente para disolver el oxígeno y los metales catalíticos (Ang., 1988), mientras que el hierro tanto en estado libre como unido al grupo Hemo es considerado como un fuerte prooxidante.…”
Section: I35 Evaluación De La Oxidación Lipídica En La Carneunclassified